Vulnérabilité de la population face aux fortes chaleurs dans l’agglomération de Kairouan (Tunisie centrale) - Mohamed Chebli; Salem Dahech; Sami Charfi (EchoGéo)
In the context of climate change, heatwaves have become intense and frequent in the Mediterranean, particularly in continental cities on the southern shore, as in Kairouan in central Tunisia. At first, this paper shows, the characteristics of hot weather in Kairouan, based on meteorological data (TX and TN) recorded by the city's synoptic station and covering the period 1980-2023. At second, we demonstrate population susceptibility to intense heat waves, a climatic feature of the city throughout the summer. On the other hand, he is interested in adaption strategies to this climatic hazard. In order to accomplish our goals, we relied on responses to a survey given to 425 residents evenly distributed over the population scale. After that, we correlated the socioeconomic and urban design parameters with the heat vulnerability factors. This study shows an intensification of summer heat and an increased frequency of long-lasting heatwaves, particularly over the last three years. In addition, the degree of vulnerability varies with location; the population living in unplanned neighbourhoods is the most vulnerable. The levels of adaption during heat waves are dependent on the citadins' level of life.